Mechanical drilling of glaciers with bottom-hole scavenging with compressed air - A. V. Bolshunov; D. A. Vasilev; S. A. Ignatiev; A. N. Dmitriev; N. I. Vasilev (Лëд и снег)
Forecasting of the Earth's climate change is important for many spheres of human activity but this cannot be successful without reliable paleoclimatic information, an important source of which is the ice core material obtained during drilling of glaciers. The process of core sampling from the upper permeable snow-firn layers of glaciers is complicated by huge losses of the drilling fluid. One of the possible solutions to this problem is using of compressed air to clean the borehole and transport the slime up to the surface due to its easy replenishment. A review and analysis of international experience in mechanical ice drilling using compressed air as a cleaning agent has shown that the method under consideration has a number of disadvantages (loss of air in permeable glacier layers, accumulation of heavy rime and formation of ice sticking) that limit its use. However, the scheme of air reverse bottom-hole air circulation, first applied by scientists from the St. Petersburg Mining University on the dome of the Academy of Sciences Glacier (the Severnaya Zemlya archipelago) is free of the above disadvantages. To adapt this method to conditions of drilling in Antarctica, it is necessary to carry out a complex of researches, the implementation of which will allow creating a new cable-suspended electromechanical drill for efficient and environmentally friendly drilling of the upper layers of glaciers.